The perceived effectiveness of alternative executive coaching approaches on personal leadership of executives in South African banks - Ramarou, Ivy Ntombifuthi (My University, 2021)
The purpose of this research was to understand the perceived effectiveness of alternative executive coaching approaches on personal leadership of executives in South African banks. Coaching forms part of the leadership development interventions and it is growing in popularity in South Africa. Coaching approaches that are consumed by South Africans were developed in the west. It is therefore important for South Africans to integrate their own worldview and context to benefit from coaching. In order for a coaching engagement to be successful, there are four (4) dimensions that need to be present; the first(1st) dimension is the coach and the coachee; the second(2nd) dimension is the models and techniques; the third(3rd) dimension is the crucial role that language and culture play during coaching interventions; and finally, the fourth(4th) dimension refers to the role organisations and families play in enabling coached individuals to thrive. A qualitative methodology was used as a preferred approach for this study. Semi-structured interviews were used to collect data in order to understand the lived experiences and perceptions of participants’ preferred coaching approaches. The total number of participants was fifteen (15). A snowball sampling method was used to get suitable participants for the study. The themes that emerged from the study were self-awareness, coaching a person as a whole, the role non-verbal cues play in coaching, self-limiting beliefs, solution orientated coaching, suitable coaching approach and lastly, improved confidence levels of a leader post coaching
A research report submitted to the Faculty of Commerce, Law and Management, University of the Witwatersrand, in partial fulfilment of the requirements for the degree of Master of Management (in Business Executive Coaching), 2021
Keywords: Executive coaching; Ontological coaching; Cognitive behavioural coaching; Solution focused coaching; Personal leadership; Whole-person; Self-awareness; SDG-8: Decent work and economic growth